Changing the Narrative, Again: Transitions and Transformations - Schuurman, Anton (TSEG - The Low Countries Journal of Social and Economic History, 2022)
In this article I argue that the development of postmodernism and the return of the narrative in the1970s did not just happen for internal scientific reasons but were a reaction to the societal developments and theories at the time. To this end I use the contemporary criticism concerning postmodernism by Beck and Giddens. In the second part I highlight three monographs to argue that social science history in recent decades also renewed itself against this background, thus helping us to understand our contemporary world in which questions of transitions and transformations are central. They use history to inform and diagnose our current situation, which they therefore need to understand as an ongoing process, though not necessarily a continuing one.